Introduction to Climate Information Services for Agriculture: Reference Guide - Hansen, Jim (2023)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project aims to enhance access to climate information services and validated climate-smart agriculture technologies in Africa, to help these countries strengthen the resilience of their agricultural sectors to the threat posed by climate change. Strengthening the capacity of next users, particularly agricultural extension and advisory service (EAS) providers who work to support farmers in Senegal and five other target countries, is crucial for achieving this goal. Towards these ends, the AICCRA project has been working to co-design and co-implement curricula targeting the agricultural extension systems to build foundational knowledge and skills to manage climate risk.